2014
DOI: 10.1002/2014jb011427
|View full text |Cite
|
Sign up to set email alerts
|

Variability of fault slip behavior along the San Andreas Fault in the San Juan Bautista Region

Abstract: An improved understanding of the time history of fault slip at depth is an essential step toward understanding the underlying mechanics of the faulting process. Using a waveform cross-correlation approach, we document spatially and temporally varying fault slip along the northernmost creeping section of the San Andreas Fault near San Juan Bautista (SJB), California, by systematically examining spatiotemporal behaviors of characteristically repeating earthquakes (CREs). The spatial distribution of pre-1998 SJB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 85 publications
1
38
0
Order By: Relevance
“…The SAF near San Juan Bautista may be especially prone to such large afterslip. As noted above, large postseismic slip has been observed for three M 5–6 earthquakes on creeping sections of the San Andreas and Calaveras Faults: the 1998 San Juan Bautista, 2004 Parkfield, and 2007 Alum Rock earthquakes [ Langbein et al , ; Freed , ; Barbot et al , ; Murray‐Moraleda and Simpson , ; Taira et al , ]. Small earthquakes on other faults may have smaller afterslip.…”
Section: Discussionmentioning
confidence: 99%
“…The SAF near San Juan Bautista may be especially prone to such large afterslip. As noted above, large postseismic slip has been observed for three M 5–6 earthquakes on creeping sections of the San Andreas and Calaveras Faults: the 1998 San Juan Bautista, 2004 Parkfield, and 2007 Alum Rock earthquakes [ Langbein et al , ; Freed , ; Barbot et al , ; Murray‐Moraleda and Simpson , ; Taira et al , ]. Small earthquakes on other faults may have smaller afterslip.…”
Section: Discussionmentioning
confidence: 99%
“…Repeating earthquakes have nearly identical waveforms, magnitudes, and source locations and have been found in a number of tectonic settings including the San Andreas Fault, California, [ Bufe et al , ; Vidale et al , ; Nadeau and Johnson , ; Schaff et al , ; Bürgmann et al , ] and the Japan Trench [ Igarashi et al , ; Uchida et al , ; Uchida and Matsuzawa , ]. Sequences of repeating earthquakes respond to large nearby earthquakes with decreasing recurrence intervals that gradually recover to premainshock rates, consistent with their being driven by frictional afterslip [ Schaff et al , ; Nadeau and McEvilly , ; Uchida et al , ; Chen et al , ; Taira et al , ; Uchida et al , ]. Additionally, variations in recurrence intervals were correlated with independent geodetic measurements of fault creep [ Nadeau and McEvilly , ].…”
Section: Introductionmentioning
confidence: 99%
“…Equation provides the slip at the interface, whereas a piecewise least squares linear fit provides an estimate of the slip rate. Our repeating earthquake catalog shows that the 2012 Ometepec and 2014 Tecpan earthquakes significantly increased the rate of repeating earthquake occurrences, a well‐known consequence of the sudden release of stress accumulation after a large event [ Schaff et al , ; Lengliné and Marsan , ; Okada et al , ; Chen et al , ; Taira et al , ]. The slip rate after the 2012 Ometepec earthquake largely exceeded the background convergence rate of 5.9 cm/yr [ DeMets et al , ], which indicates postseismic slip after the main shock.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified repeating earthquakes in a large variety of tectonic environments including California [ Vidale et al , ] Japan [ Uchida et al , ; Matsuzawa et al , ; Kimura et al , ], China [ Schaff and Richards , ], Taiwan [ Chen et al , , ], Turkey [ Peng and Ben‐Zion , ], and Tonga‐Vanuatu [ Yu , ]. Here repeating earthquakes have been observed along the creeping segment of the San Andreas Fault [ Nadeau and Johnson , ; Schaff et al , ; Rubin et al , ; Taira et al , ] and along the Calaveras fault [ Vidale et al , ; Marone et al , ; Schaff and Beroza , ; Peng et al , ; Zhao and Peng , ; Templeton et al , ]. Characteristic repeating sequences in these environments have been exploited as a common framework to explore the physical mechanism behind their origin and occurrence [ Sammis and Rice , ; Beeler et al , ].…”
Section: Introductionmentioning
confidence: 99%